A Cognitive Approach to the Event Structures of Wh-dialogic Constructions. Issue 4 (23rd December 2016) - Zeng, Guocai
Abstract: In English, the linguistic unit of a wh-question and one of its answers functions as a dialogic construction in terms of the pairing of form and meaning or form and function. The fact that the linguistic resources in a wh-question are repeated in its answer implies the degree of structural coupling of events between wh-question and the answer, showing the evidence of cooperation between two speakers at the syntactic level. This paper, from the integrated perspective of the event-domain cognitive model and schema-instance cognitive view, has investigated the Event-based Schema-Instance cognitive model (ESI) for this kind of dialogic construction. Meanwhile, based on the different types of answers to wh-questions in these dialogic constructions that are collected from Corpus of Contemporary American English (COCA), this paper attempts to explore the connection of the degree of event structural coupling with the type of speakers' cooperation of syntax-level in English wh-dialogues. The corpus-based analysis indicates that, among 5 051 natural wh-dialogues, cases of full syntax-level cooperation between speakers in English conversations are the most frequently seen, while those of partial cooperation of syntax level between speakers are the second, and wh-dialogues with non-syntactic cooperation between speakers are the least found, demonstrating the interaction of linguistic structure, cognitive process and interpersonal communication, meanwhile revealing certain features of the pragmatic use of English wh-dialogic constructions in conversations.